Development of software system for detecting defective symbols on integrated circuit chip with adjustable readability level - Aris, Ishak; Azri, Maaspaliza; Hasan, Zainab; Hasan, M. K.; Khalid, Marzuki; H. M. Amin, Shamsudin; Cyril, H. A. (2005)
In semiconductor fabrication process, symbol or label inspection is one of the main processes that need to be considered seriously. Errors may occur during the printing process of label or name on the integrated circuit chip (IC). If this occurs, the IC chip may have a wrong name. Providing a reliable detection system that is able to detect the errors printed on the IC chip can solve the problem mentioned above. The symbol detection system that currently being implemented by the semiconductor industry suffers from overkilled and escaped problems. This paper presents the development of a software system, which capable of detecting the defective characters printed on the IC chip using Active Matrox Imaging Library Release 7. The proposed system has an adjustable reading level that can solve the problems mentioned above.